Is it Better to Intermarry? Immigration Background of Married Couples and Suicide Risk Among Native-Born and Migrant Persons in Sweden - Anna Oksuzyan; Sven Drefahl; Jennifer Caputo; Siddartha Aradhya (European Journal of Population, 2023)
Marriage is protective against suicide across most populations, including for persons of different ethnicities and immigrant backgrounds. However, the well-being benefits of marriage are contingent upon marital characteristics—such as conflict and quality—that may vary across spousal dyads with different immigration backgrounds. Leveraging Swedish register data, we compare suicide mortality among married persons on the basis of their and their spouse's immigration backgrounds. We find that relative to those in a native Swede-Swede union, Swedish men married to female immigrants and immigrant women married to native men are at higher risk of death by suicide, while immigrants of both genders who are married to someone from their birth country have a lower risk of suicide mortality. The findings support hypotheses about the strains that may be encountered by those who intermarry, as well as the potential selection of individuals into inter- and intra-ethnic marriages.
Keywords: 300; Suicide; Immigrant; Intermarriage; Mental health register data; Sweden